Isolation and Cs+ resistance mechanism of Escherichia coli strain ZX-1 - Kojima, Daiki; Tanaka, Shunsuke; Kurosaki, Ayane; Zhiyu, Xiong; Ito, Masahiro (Frontiers in Microbiology, 2024)
This research aims to elucidate the physiological mechanisms behind the accidental acquisition of high-concentration cesium ions (Cs+) tolerance of Escherichia coli and apply this understanding to develop bioremediation technologies. Bacterial Cs+ resistance has attracted attention, but its physiological mechanism remains largely unknown and poorly understood. In a prior study, we identified the Cs+/H+ antiporter TS_CshA in Microbacterium sp. TS-1, resistant to high Cs+ concentrations, exhibits a low Cs+ affinity with a Km value of 370 mM at pH 8.5. To enhance bioremediation efficacy, we conducted random mutagenesis of TS_cshA using Error-Prone PCR, aiming for higher-affinity mutants. The mutations were inserted downstream of the PBAD promoter in the pBAD24 vector, creating a mutant library. This was then transformed into E. coli-competent cells. As a result, we obtained a Cs+-resistant strain, ZX-1, capable of thriving in 400 mM CsCl—a concentration too high for ordinary E. coli. Unlike the parent strain Mach1TM, which struggled in 300 mM CsCl, ZX-1 showed robust growth even in 700 mM CsCl. After 700 mM CsCl treatment, the 70S ribosome of Mach1TM collapsed, whereas ZX-1 and its derivative ΔZX-1/pBR322ΔAp remained stable. This means that the ribosomes of ZX-1 are more stable to high Cs+. The inverted membrane vesicles from strain ZX-1 showed an apparent Km value of 28.7 mM (pH 8.5) for Cs+/H+ antiport activity, indicating an approximately 12.9-fold increase in Cs+ affinity. Remarkably, the entire plasmid isolated from ZX-1, including the TS_cshA region, was mutation-free. Subsequent whole-genome analysis of ZX-1 identified multiple SNPs on the chromosome that differed from those in the parent strain. No mutations in transporter-related genes were identified in ZX-1. However, three mutations emerged as significant: genes encoding the ribosomal bS6 modification enzyme RimK, the phage lysis regulatory protein LysB, and the flagellar base component protein FlgG. These mutations are hypothesized to affect post-translational modifications, influencing the Km value of TS_CshA and accessory protein expression. This study unveils a novel Cs+ resistance mechanism in ZX-1, enhancing our understanding of Cs+ resistance and paving the way for developing technology to recover radioactive Cs+ from water using TS_CshA-expressing inverted membrane vesicles.